Studies on Physiochemical Property of Cow Milk: A Case Study of Dehradun City (Uttarakhand) - Sonu Dwivedi; Rakesh Singh; Yashrab; Shubham Saklani; Prashant Singh; Bhavtosh Sharma (International Journal of Scientific Research in Chemistry, 2025)
Milk is a dilute emulsion consisting of an oil/fat dispersed phase and an aqueous colloidal continuous phase. The physical properties of milk are similar to those of water but are modified by the presence of various solutes (proteins, lactose and salts) in the continuous phase and by the degree of dispersion of the emulsified and colloidal components. Dehradun is generally safe from any type of milk adulteration however with growing demand of cow milk recommend to ensure the continued compliance with quality standard. The aim of this study was to investigate the physicochemical properties of cow milk produced and marketed in Dehradun City, Uttarakhand. A total of 04 samples of raw cow milk were collected randomly from selected dairy farms from four study sites in the Dehradun City. The principal physiochemical properties of milk include its density, pH, surface tension, viscosity, electrical conductivity and presence of urea, phosphate, sulfate and calcium. The analysis focus on these properties. The obtained results showed that there were significant differences in calcium, urea, pH and surface tension observed in temperature 28°C), between dairy farms milk samples, respectively. The most physicochemical quality of the examined milk sample of site A and B were within the acceptable levels while that of site D was best except milk samples from site C the value electrical conductivity and urea in milk samples were high i.e. 81 mg/100ml (calculated) compare to 14-28 mg/100ml (standard value) implying poor milk quality and can be a sign of animal health issues or adulteration while the value for viscosity and calcium is low i.e. 1.391 cP/cm (standard value 1.5-2.5 cP/cm) and 86 mg/100ml (standard value 120-150 mg/100ml) which imply decreased quality and nutritional or metabolic issues. While the milk quality of site C was very poor and needed to be avoided. Therefore, this suggests the need for improved hygienic practice and educating the public on safety issues to minimize risk of food borne illnesses and maintain product integrity.
Keywords: Cow milk; Health; Physiochemical properties; Quality